Viver sem Deus e sem Religião: a vida possível no ateísmo (Living without God and religion: the possibility of atheism) - DOI: 10.5752/P.2175-5841.2010v8n18p85 - Ferreira, Amauri Carlos (Horizonte, 2010)
Is it possible to live without God? Is it possible to live without religion in the midst of faithful? Starting from the premise of conflict, not dialogue, between religion and science, the author uses the ideas of Bertrand Russell to support affirmative answers to these questions. When the notion of the good life is based on the provisional truth of science, rather than on religion, the faithful and the ecclesiastic representatives postulate the truth of faith using emotional and fallacious arguments. The conflict between religion and science arises with the perception that human truth is based on processes, errors and successes, not on certainties. The conviction of the existence of God and of a divine plan is justified by emotional arguments, in general accompanied by acts of cruelty and violence, as we know from history. In order to improve our understanding of how the faithful attempt to justify their emotional arguments, the author cites Russell's case, when the philosopher was prevented from teaching at the College of the City of New York (CCNY), in the 1940s due to his anti-religious ideas.